2020
DOI: 10.3390/ani10040563
|View full text |Cite
|
Sign up to set email alerts
|

Negative Energy Balance Influences Nutritional Quality of Milk from Czech Fleckvieh Cows due Changes in Proportion of Fatty Acids

Abstract: The objective of this study was to evaluate the influence of negative energy balance on fatty acids proportion in the milk of Czech Fleckvieh cows after calving. Milk quality was determined based on fatty acid group proportion. Milk quality was evaluated in relation to selected negative energy balance (NEB) traits: body condition change (DEC) and milk citric acid content (CAC) after calving. Milk samples (n = 992) were collected once per week from 248 Czech Fleckvieh cows during the first month of lactation. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Adipocytes then release FAs that are usually unfavorable for the nutritional quality of milk fat. Ducháček et al [ 14 ] showed that NEB increased the share of hypercholesterolemic FAs in the milk of HF cows by 1.86 p.p. on average.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adipocytes then release FAs that are usually unfavorable for the nutritional quality of milk fat. Ducháček et al [ 14 ] showed that NEB increased the share of hypercholesterolemic FAs in the milk of HF cows by 1.86 p.p. on average.…”
Section: Discussionmentioning
confidence: 99%
“…This induces lipolysis of adipose tissue [ 8 ] and causes a sharp decline in BCS, which is conducive to the release of oleic acid from the adipocytes [ 9 , 11 ]. Research by Ducháček et al [ 14 ] and Vernon [ 15 ] shows that this process need not adversely affect the nutritional value of milk, but it does affect the overall health of cows [ 14 ]. Excessive lipolysis of adipose tissue is conducive to the production of non-esterified fatty acids (NEFAs) [ 9 ], probably because the FA profile of milk is determined at many levels.…”
Section: Introductionmentioning
confidence: 99%
“…The parts were then transported to the university meat production lane and aliquot samples (300-500 g) of muscle (musculus longissimus lumborum et thoracis; collected at the last rib), liver, heart, and visceral (pelvic) adipose tissue (VAT) were taken. 5 8.2 7.5 Methionine 5 2.6 2.4 Fat 6 36 108 Crude fiber 7 65 60 Ash 48 44 Calcium 5 6.0 5.5 Phosphorus 5 4.3 4.0 Sodium 5 1.6 1.5 Nitrogen-free extractives 8 707 655 4 determined using KD-310-A-1015 KjelROC Analyzer (Furulund, Sweden); 5 declared by the producer; 6 hexane/2-propanol extract; 7 determined using ANCOM220 Fiber Analyzer (Ancom Technology, Macedon, NY, USA); 8 calculated as a remainder to 100%; 9 calculated from nutrient content.…”
Section: Animals Diets Sample Collectionmentioning
confidence: 99%
“…In monogastric animals, tissue fatty acid profiles closely reflect the fatty acid profiles of their diets [7]. Changes in animal nutrition by addition of fat sources with a favorable ratio of PUFA n-6/n-3 can lead to positive changes in the composition of animal products, such as milk [8], eggs [9], and meat [10].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of milk fat was previously monitored mainly due to the assessment of the nutritional properties of milk and its potential health benefits/risks for consumers and its technological properties, which affect milk processing [ 1 , 23 , 24 , 25 ]. Recently, the FA proportion in the milk fat has also been considered in connection with the metabolic status of dairy cows, the prediction of milk quality from different farm production systems, geographical origins, and the contribution of dairy cows to climate change (methane emissions) [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%